Karakteristik Campuran SMA Kasar Menggunakan Batu Sungai Sa’dan Kecamatan Sesean Toraja Utara - Arung Dating Sandabunga; Nur Ali; Rais Rachman (Paulus Civil Engineering Journal, 2020)
The methodology in this study is to conduct a series of characteristic tests in the form of rough aggregates, fine aggregates, fillers and asphalt and then design the composition of the mixture then make the test objects in the form of rough Stone Matrix Asphalt mixture as well as Marshall testing to obtain Immersion Index / Residual Strength Index / Blend durability using optimum asphalt levels.The results of the research showed the characteristic material meets Bina Marga General Specification 2018 as a layer material of road hardening. Through the marshall test obtained characteristics of Stone Matrix Asphalt Rough mixture with asphalt levels of 6.00%, 6.25%, 6.50%, 6.75%, and 7.00%. Marshall Immersion mixed Stone Matrix Asphalt Rough test results with optimum asphalt rate of 7.00% obtained Time Strength Index of 97.53% which meets Bina Marga General Specification 2018 which is at least 90%.